2015
DOI: 10.1051/0004-6361/201424705
|View full text |Cite
|
Sign up to set email alerts
|

Shell instability of a collapsing dense core

Abstract: Aims. Understanding the formation of binary and multiple stellar systems largely comes down to studying the circumstances under which a condensing core fragments (or not) during the first stages of the collapse. However, both the probability of fragmentation and the number of fragments seem to be determined to a large degree by the initial conditions. In this work we explore this dependence by studying the fate of the linear perturbations of a homogeneous gas sphere, both analytically and numerically. Methods.… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 48 publications
0
9
0
Order By: Relevance
“…Tidal forces have been advocated in various contexts to either limit or quench star formation (Bonnell & Rice 2008;Ballesteros-Paredes et al 2009), but also, conversely, to trigger it (Jog 2013;Renaud et al 2014). Ntormousi & Hennebelle (2015) discussed the influence of the density distribution and showed that in a collapsing cloud, the tidal forces tend to be initially compressive, which promotes fragmentation, and then the forces become stabilizing. The key quantity to study the influence of tidal forces is the gravitational stress tensor, ∂ i g j , which is characterized by the three eigenvalues, λ i .…”
Section: Tidal Forcesmentioning
confidence: 99%
“…Tidal forces have been advocated in various contexts to either limit or quench star formation (Bonnell & Rice 2008;Ballesteros-Paredes et al 2009), but also, conversely, to trigger it (Jog 2013;Renaud et al 2014). Ntormousi & Hennebelle (2015) discussed the influence of the density distribution and showed that in a collapsing cloud, the tidal forces tend to be initially compressive, which promotes fragmentation, and then the forces become stabilizing. The key quantity to study the influence of tidal forces is the gravitational stress tensor, ∂ i g j , which is characterized by the three eigenvalues, λ i .…”
Section: Tidal Forcesmentioning
confidence: 99%
“…We introduce a simple spherically symmetric model invoking accretion onto the cloud core. Ntormousi & Hennebelle (2015), based on Larson (1969), give the time-dependent density of an accreting cloud as Figure C1. Numerical solutions for the radial evolution of the ionisation front in Equation B1 assuming cloud properties as given in Section 3.…”
Section: Appendix D: Collapsing Ionisation Frontsmentioning
confidence: 99%
“…It should be noted that the fragmentation process is complex even in the idealized case of homologous collapse (see Hanawa & Matsumoto 1999;Ntormousi & Hennebelle 2015). This means that our method of finding self gravitating subregions using Eq.…”
Section: Collapse: Criterion and Evolutionmentioning
confidence: 99%